Impact of Intermediate Cystic Fibrosis Classification on Parents' Perceptions of Child Vulnerability and Protectiveness. (May 2019) - Tluczek, Audrey; Levy, Hara; Rock, Michael J.; Ondoma, Cissy; Brown, Roger L.
This cross-sectional, mixed-method study examined factors associated with parent perceptions of child vulnerability and protectiveness in three groups: cystic fibrosis (CF-group, n = 40), intermediate CF classification (I-group, n = 20), and healthy (H-group, n = 50). A composite indicator structural equation (CISE) using Bayesian estimation tested two mediational models: psychological and biological. Significant results ( p < .05) from the psychological model showed I-group and CF-group parents perceived their children to be more vulnerable than H-group parents but reported lower levels of protectiveness than H-group parents. Perceptions of vulnerability mediated protectiveness for CF- and I-groups. The biological model showed I-group children had significantly less severe genotype and phenotype, and lower sweat chloride levels than the CF-group; I-group parents had lower expectations about children developing CF symptoms. Both models showed negative associations between children's ages and protectiveness. Psychological factors explained perceptions of child vulnerability and protectiveness; biological factors explained protectiveness. Parent perceptions of vulnerability and protectiveness are separate, independent constructs.